A formação de professores em Educação Física no Plano Nacional de Formação de Professores da Educação Básica-PARFOR/UNEB: realidade, tensões e contradições - Sousa, Itamar Silva de (2014)
This research aims to study the design of training teachers in this Plano Nacional de Formação de Professores da Educação Básica - PARFOR, the degree course in Physical Education from the Universidade do Estado da Bahia, UNEB, Departamento de Ciências Humanas, Jacobina-Ba. This research is mainly aimed to critically analyze the design of teacher training that guides PARFOR and how that concept hinges on the development of Supervised Physical Education course. For this, we used injections of critical design-dialectical, in that the categories of the method, all, contradiction, mediation and hegemony were in basic research. Analysis of curricular course design and realization of Focus Group 7 with student teachers from PARFOR: as a way of apprehending the reality of the data two instruments was used. Results show that the Physical Education course PARFOR sets of approaches with a conception of teacher-centered hegemonic pedagogical approaches, the "know-how" from the practical experiences of everyday school life. Further evidence that teacher education has been characterized by relief and lack of theoretical development of pedagogical-didactic character essential in teacher education. It was found, therefore, that the teaching practice of the course have not allowed a theory-practice linkage in the training process of teachers in a perspective of praxis